2023
DOI: 10.3390/diagnostics13152519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Osteoporosis Parameters in Plain Hip Radiography and DXA Results in 156 Patients at a Single Center in Turkey

Abstract: Background: The aim of the current study is to determine the relationship between osteoporosis findings in plain X-ray and dual-energy X-ray absorptiometry (DXA) measurement results and to create an alternative diagnostic method for osteoporosis without DXA measurement when necessary. Methods: DXA values and hip radiographs of 156 patients were retrospectively analyzed. Singh index (SI), Dorr index (DI), cortical thickness index (CTI), and canal-to-calcar ratio (CCR) measurements from both plain hip radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the mean age of these studies was relatively young and ranged between 64 and 72 years, which does not represent the most vulnerable age. A recent study by Ilyas et al confirmed the correlation between reduced BMD and CTI, whereas they did not examine fractured proximal femora in a cohort of 156 patients with a mean age of 68 years [25]. Although the current mean age of patients with proximal femoral fractures is 75 years, the health system will be challenged by a growing population of even older patients in the upcoming years [26].…”
Section: Discussionmentioning
confidence: 98%
“…However, the mean age of these studies was relatively young and ranged between 64 and 72 years, which does not represent the most vulnerable age. A recent study by Ilyas et al confirmed the correlation between reduced BMD and CTI, whereas they did not examine fractured proximal femora in a cohort of 156 patients with a mean age of 68 years [25]. Although the current mean age of patients with proximal femoral fractures is 75 years, the health system will be challenged by a growing population of even older patients in the upcoming years [26].…”
Section: Discussionmentioning
confidence: 98%
“…Although SI suffers from inaccurate estimates, i.e. low sensitivity, it has a high specificity which allows its use as an indicator of osteopenia [ 32 , 34 , 35 ]. However, this index cannot stand alone and should be utilized in combination with other tools such as DEXA when diagnosing osteoporosis [ 33 ].…”
Section: Main Textmentioning
confidence: 99%